Source rock characterization and oil generating potential of the Jurassic Madbi Formation, onshore East Shabowah oilfields, Republic of Yemen - Hakimi, M.H.; Abdullah, W.H.; Shalaby, M.R. (Elsevier, 2010)
The hydrocarbon source rock potential of shales from the Jurassic Madbi Formation was evaluated using organic geochemistry (Rock-Eval pyrolysis, TOC and bitumen extraction) and organic petrology. Very good source rock potential is suggested by high values of total organic carbon content (TOC, >2.0 wt%) and high extractable organic matter content and hydrocarbon yields (>11,000 and 6000 ppm, respectively). The Madbi Formation samples have high hydrogen index (HI) and low oxygen index (OI) values. Most of the samples in the study area are thermally mature and contain oil prone Type I and Type II kerogen. Vitrinite reflectance (Ro) values for the Madbi shale samples were measured from 0.74% to 0.89%. T(max) values range from 430 to 438 degrees C, which are in reasonably good agreement with vitrinite reflectance data, reveal that the Madbi shales are at the early to peak mature stage. On the basis of biomarker maturity parameters, these shales are thermally mature. Shales of the Madbi Formation contain abundant hydrogen rich kerogen (liptinite up to 55%) and therefore good oil generating potential is anticipated. This is supported by high hydrogen indices (HI) of up to 400 mg HC/g TOC and early to peak mature oil window range. (C) 2010 Elsevier Ltd. All rights reserved.